Forensic assessment of HP14 classification of waste: evaluation of two standards for preparing water extracts from solid waste to be tested in aquatic bioassays. Issue 3 (3rd July 2019) - Pivato, Alberto; Beggio, Giovanni; Raga, Roberto; Soldera, Valentina
Abstract: Misclassification of waste hazardousness could lead waste operators to be charged of illegal trafficking. Among different aspects characterizing waste hazardousness, Ecotoxicity is acknowledged as the most frequent Hazard Property classifying wastes as hazardous. In this context, a conventional, scientifically based and agreed-upon procedure for ecotoxicity assessment can help forensic activities to verify the conditions of possibly occurred illegal trafficking of waste. Currently, European Regulation declares a waste ecotoxic according to a calculation method based on its chemical composition. Whether outcomes from calculation method would result in an unrealistic assessment, results from ecotoxicity testing can be used for waste hazardousness classification. However, each Member State is allowed to establish a specific experimental procedure, thus resulting in a fragmented legal framework regulating ecotoxicological testing. This study gives a description of the two main approaches followed by European Member States in regulating ecotoxicity assessment of wastes. This work reports how both investigated approaches address three main methodological issues: which sample preparation standard must be carried out, which test battery should be performed and which concentration limits will trigger hazard classification. Further, a comparison is presented between two different standardized protocols (GHS Annex X and EN 14735) for leaching tests of solid wastes, performed on Automotive Shredder Residues (ASR) samples to obtain water extracts to be further tested in aquatic bioassays. EN 14735 resulted more conventional for routine waste classification efforts, both in terms of achieved sample representativeness and time needed to derive test portions. Then, results from chemical physical analyses on derived water extracts suggested that the lower Liquid-to-Solid ratio required by EN 14735 could have played a key role in determining the resulting higher contaminant concentrations. For this reason, it could also be considered as the most conservative approach for further testing on aquatic organisms. However, this assumption must be further validated by further research on different waste streams, speciation mechanisms of dissolved contaminants, the role of pH adjustment of the test portion and the influence of specific dilution media.